Credit Risk Analysis On Banking Financial Performance (Case Study on State-Owned Banks Listed on the IDX for the 2022-2024 Period) - Zeta, Cindy; Herwati, Helmi; Fransisca Salim, Cindy; Sesi, Sesi (Jurnal Ecoment Global, 2025)
This study aims to examine and analyze the impact of credit risk on banking financial performance, focusing on State-Owned Banks (BUMN) listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. Credit risk, measured using the Non-Performing Loan (NPL) ratio, is the main independent variable, while banking financial performance is measured using Return On Asset (ROA) as the dependent variable. Other relevant control variables such as Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), and Net Interest Margin (NIM) are also considered to provide a comprehensive picture. Based on the literature review, it is generally anticipated that credit risk will have a significant negative relationship with financial performance. However, previous studies have shown mixed findings, including insignificant or even positive relationships in some contexts. This study will contribute to clarifying this relationship in the post-COVID-19 pandemic context in Indonesia, especially for state-owned banks that have a strategic role in the national economy.